ANALISIS GAYA BAHASA PADA PUISI “KANGEN” KARYA W.S. RENDRA - Trisnawati (Universitas 45 Surabaya, 2022)
Poetry is a literary work that contains the outpouring of the heart or the expression of feelings with imaginative words that are poured into a piece of writing. Poetry is bound by rhythm, dimension, rhyme, as well as the arrangement of lines and stanzas. This article discusses the meaning of the poem